FENOMENA SOCIAL CLIMBER MELALUI TWITWAR - Fizzy Andriani (Jurnal Pustaka Komunikasi, 2018)
Social media is used as a medium of interaction in many ways, including debating or called twitwar. Some twitwar, was intentionally written by the account owner with the aim of increasing popularity or called the social climber. This study wanted to find out how twitwar was created, what topics were created, and how twitwar actors responded to their twitwar replies. This study uses the concepts of New Media, Twitwar, and Reputation in social media. This research is qualitative research and uses constructivist paradigm. The results of this study indicate that the social climber creates provocative posts for the targeted groups that are considered easily provoked, in this case KPOP fans. While the response of the twitwar actors in responding to the replies given by followers is by writing more provocative sentences, so as to provoke anger from the intended groups, thus increasing their popularity.